Ekphrasis, Fear, and Motivation in the Apocalypse of John - Stewart, Alexander E. (Bulletin for biblical research, 2017)
Recent research on ekphrasis sheds light on how John utilized vivid description to guide the imagination and stir the emotions of his hearers. This is particularly evident in John's visions of judgment and salvation. The primary grounds for John's exhortation to overcome include exclusion from or participation in final salvation. John's frequent use of ekphrasis, particularly within his visionary narratives, enables his hearers to vividly visualize and imagine the presently invisible grounds offered for John's rational argumentation, thus producing an emotional response in support of obedience and action. This article explores the use of ekphrasis in the fifth and sixth trumpets (Rev 9:1-19) to direct the hearer's imagination and create the emotion of fear in support of John's rhetorical agenda.